Phytochemical Screening And Antioxidant Activity Testing Of Porang (Amorphophallus Muelleri Blume) Leaf Ethanol Extract From Kuta Buluh Region, North Sumatera - Ainil Fithri Pulungan; Ridwanto Ridwanto; Gabena Indrayani Dalimunthe; Zulmai Rani; Rahma Dona; Ricky Andi Syahputra; Robiatun Rambe (International Journal of Health and Pharmaceutical (IJHP), 2022)
Porang (Amorphallus muelleri Blume) is one type of tuber plant that has the potential to be developed in Indonesia. Porang plants have been reported to contain chemical compounds that have antioxidant activity. This research was conducted on the leaves of the porang plant with the aim of knowing the antioxidant activity, characterization, and phytochemical profile of the compounds contained therein. Compound identification and characterization were performed using standard methods, and antioxidant activity was determined using the DPPH (1,1- Diphenyl-2-picrylhydrazyl ) method. The results of the identification of chemical compounds showed that the ethanol extract of porang leaves contained chemical compounds of alkaloids, flavonoids, tannins, saponins, and steroids. The results of the examination of the simplicia characterization of porang leaves included the soluble ethanol content of 33.93%, the water soluble extract content of 17.3%, the ash content of 5.58%, the acid insoluble ash content of 0.235% and the water content of 8%. From the results of the simplicia characterization, it shows that the results meet the specified requirements. The results showed that the ethanol extract of porang leaves had antioxidant activity with an IC50 value of 93.04 µg/mL, which in this case is included in the category of strong antioxidant activity. Meanwhile, as a comparison, Vitamin C was used, which has an IC50 value of µg/mL, which is included in the category of very strong antioxidant activity.